Rhodoxanthin as a characteristic keto-carotenoid of manakins (Pipridae) - Hudon, Jocelyn; Storni, Alline; Pini, Elena; Anciães, Marina; Stradi, And Riccardo (Auk, 2012)
Manakins are small suboscine passerines renowned for elaborate courtship displays and pronounced sexual dichromatism. We extracted and identified the carotenoid pigments found in the bright yellow to red feathers of 15 Neotropical manakin species. Rhodoxanthin (4',5'-didehydro-4,5'-retro-β,β- carotene-3,3'-dione) of a deep red hue was widely found in the plumages of these birds. The 4-keto-carotenoids typically found in red plumages (α-doradexanthin, astaxanthin, canthaxanthin, etc.) were found in only the Flame-crested Manakin (Heterocercus linteatus) and the Red-headed Manakin (Pipra rubrocapilla). Rhodoxanthin was recently identified in the Pin-tailed Manakin (Ilicura militaris). Hudon et al. (2007) suggested that the Pin-tailed Manakin produces rhodoxanthin endogenously from dietary carotenoids, and this suggestion now finds some support in the pigment's wide and specific distribution in manakins. It is possible that this capacity arose in a common ancestor of manakins and cotingas, given that rhodoxanthin also occurs in the feathers of red cotingas (Phoenicircus spp.). Feathers with rhodoxanthin absorbed longer wavelengths of light than those with 4-ketocarotenoids, but not in Pipra, which has species with one or the other type of keto-carotenoids. We found that feathers with rhodoxanthin also contained e, e-caroten-3(3')-ones (e.g., canary-xanthophyll B and the recently described piprixanthin), which are believed to be intermediates along the rhodoxanthin pathway. Manakins thus have the capability to produce a wide range of carotenoid pigments and bright yellow to red colors, on which natural and sexual selection may act. © The American Ornithologists' Union, 2012. Printed in USA.
Keywords: Carotenoid; Chemical Analysis; Feather; Passerine; Pigment; Plumage; Sexual Selection; Aves; Heterocercus Linteatus; Ilicura Militaris; Phoenicircus; Pipra; Pipra Rubrocapilla; Pipridae